Module functional and potential characteristics of condensers in the region; correlations between them - Zory , N. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A series of new statements about relations between the known modulus, functional, and potential characteristics of space condensers are proved. A theorem on the continuity of the moduli of special families of curves is established.